Arqueologia da escrita de João Antônio: Um projeto estético e político - Giordani, Rosselane Liz (2021)
Dive into the labyrinths of the poetics of a writer who turned his work into a politicalaesthetic act. In this research gesture, we delve into the universe of the writer and journalist João Antônio Ferreira Filho, an exponent in Brazilian literature of the 1960s and 1970s for exacerbating in his writing the soul of a forgotten people, of an underworld undermined by the discourse of progress and development. . The objective of this research is to look behind the scenes of his literary creation, revealing nuances of his trajectory as a journalist and writer that reverberated in the composition of his writing. The guiding thread of this trajectory intertwines his trajectory in journalism and his permanent wandering through urban landscapes, impregnated with a melancholy and scathing look at social reality. We investigate how the writer-subject is shaped and crossed by historical time, while his writing carries marks of his experiences, constituting a literary writing that transits the shifting frontiers of autobiography and autofiction. The João-Antonian narrator transits and intertwines memories and social perceptions and re-elaborates them, in a writing that moves through a wanderernarrator who transits through the urban landscape and through the author's memories. The research paths put us at the forefront of a hybrid narrative: between memories, autobiographies, historical and documentary records, re-creations of the urban landscape and its survivors, as well as the exacerbation of his feeling about the bare reality. To undertake the analysis, we focus on manuscripts, from the methodological approach of Genetic Criticism. We intertwine the writing movements from the composition of a dossier, which permeates interviews published in newspapers, correspondence with friends and critics, in which the writer records his ideas about literature, journalism and the composition of his characters, as well as fragments of works published in books. The course of the research puts biographical fragments of his personal trajectory into an interface, which is crossed by his perception of social marginality, resulting in an aesthetic and political project. The search for a cartography of writing movements leads us to a theoretically based composition. We start from the reflections of Genetic Criticism as a methodological basis (Louis Hay, Almuth Grésillon, Phillipe Willemart, Cecília Salles), which also repositions the subject of writing. We intertwine biographical fragments to recompose his training trajectory, and which will lead to his writing. From their experiences and critical look at social reality, in the faceto-face with life arises a literature of reality tattooed with the mark of marginality, from which we seek an interface with theoretical reflection subsidized by Aníbal Quijano and Antônio Cândido. From this dimension of writing reverberates its political and aesthetic project, and the reflections on form and content, which we seek support in Georg Lukács and Fredric Jameson. From the writer's relationship with the social to the implosion of form, a hybrid writing pulses that materializes through a wanderernarrator, a central figure in his creative process of autofiction. Category this central that we will seek support in Walter Benjamin, Serge Doubrovsky, Philippe Lejeune and Anna Faedrich.